Mixed-method Irish study exploring the role of diet in IBD based on an online questionnaire and a patient panel opinion - Kevin Moore; Majella O’Keeffe; Naomi Hanrahan; Victoria Spillane; Mick Dineen; Aoife Murphy; Ana Velikonja; Margot Hurley; Silvia Melgar (BMJ Open Gastroenterology)
Objective Diet is a risk factor in inflammatory bowel diseases (IBD) pathogenesis. This study aims to examine the dietary patterns and beliefs of Irish patients living with IBD through an online questionnaire and subsequent open discussions with an IBD patient collaborator panel (PCP). All data presented here are selected and presented following the PCP’s suggestions and views.Design This mixed-method study included an online questionnaire using a short food frequency questionnaire examining dietary patterns, dietary opinions, beliefs and behaviours (phase I). Six in-person PCP sessions were conducted, where findings from the online questionnaire, diet and lifestyle in the context of IBD were discussed in depth (phase II).Results The questionnaire revealed that respondents with active IBD are associated with the consumption of high-sugar, processed and meat-based foods while reducing their consumption of high-fibre foods. Individuals with active Crohn’s disease have a decrease in overall daily energy consumption and a significant reduction in intake of fibre, non-starch polysaccharides, micronutrients [B vitamins (B1, B2, and B9), vitamin C, calcium] and trace elements (iron, zinc, copper and manganese). The PCP reported that food tolerability is limited during relapse, leading patients to prefer simple carbohydrates for energy, consistent with the dietary intake data. The PCP reported that most dietary advice was received during hospitalisation (relapse), focused on food avoidance, with little follow-up during remission. The consensus among the PCP was that factors, such as disease type, psychological aspects, dietary understanding and support, can influence peoples’ dietary choices.Conclusion In summary, we show that dietary intake in people with IBD varies and may depend on several factors, not just the disease itself. This PCP desires more dietary information and professional support outside of hospitalisation to assist with disease management.